(untitled) (International Journal of Engineering and Computer Science, 2019)
One of major component of operating system is task scheduling for the optimum utilization of the resources. Round Robin had been an effective task scheduling method so far, but it has certain limitations. It uses static time quantum which sometimes leads to starvation. The proposed Optimised Round Robin is a modified version of the existing Round Robin scheduling which results in better average time and average turnaround time and overall increase in the performance. The comparative analysis is being done that indicates ORR gives improvement in the system performance.